Takhrij and Syarah Hadith Agrotechnology Leasing Land, Planting, and Land Management - Nuke Nurasiah Jamil; Wahyudin Darmalaksana; Suryaman Birnadi (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith with regard to agro-technology. The method of this research is one type of literature study and field study with the takhrij and sharah hadith approaches. The results and discussion of this study are the main natural sources, namely soil and water that are easily damaged or degraded along with the anticipation to overcome soil damage by carrying out good land management. The conclusion of this study is the hadith takhrij and syarah about farming and the effect of land management.